Organic Matter Integration, Overprinting, and the Relative Fraction of Optically Active Organic Carbon in a Human-Impacted Watershed - Eckard, Robert S.; Bergamaschi, Brian A.; Pellerin, Brian; Spencer, Robert G.; Dyda, Rachel; Hernes, Peter J. (Frontiers in Earth Science, 2020)
Rivers continually integrate terrestrial organic matter (OM) into their waters, in a process that transfers 1.9 Pg C yr-1, as the primary linkage between oceanic and terrestrial carbon cycles. Yet rivers are not simple, conservative OM integrators. Patchy local land uses (wetlands, bogs, agriculture) release OM that can disproportionately alter river biogeochemistry and overprint upstream carbon. These releases are quantifiable at the plot scale but remain unpredictable across river reaches and watersheds, critically inhibiting our ability to scale up terrestrial-aquatic linkages to regional/global carbon cycling models. We evaluated OM overprinting distance along a human-influenced watershed to quantify river integration of terrestrial OM and to bridge the quantification gap between habitats and waterway biogeochemistry. We investigated changes in dissolved organic carbon (DOC) concentration and dissolved organic matter (DOM) composition (lignin phenols, excitation-emission spectra using parallel factor analysis [PARAFAC], and the relative fraction of optically active DOM [EEMDOC]). DOC concentrations increased continually (p<0.001) downstream, from median 1.0 mg L-1 at 30 km (headwaters) to 3.3 mg L-1 at the river mouth. This rate of increase corresponded to a DOC overprinting distance—the longitudinal distance over which DOC concentrations double—of 13 km. Mainstem DOC overprinting distance ranged from 8 km (winter, rainy season) to 21 km (summer, dry / irrigation season), highlighting stronger overprinting during increased hydraulic connectivity. Stronger overprinting also correlated to higher EEMDOC (p<0.001). Overprinting distance effectively quantifies river integration of DOM along the terrestrial-aquatic interface, helping to refine bottom-up carbon cycle estimates, inform upscaling of site-specific fluxes, and track land use and climate influence on river biogeochemistry.